Anticonvulsant action of both NMDA and non-NMDA receptor antagonists against seizures induced by homocysteine in immature rats - Folbergrová, J (Experimental neurology, 1997)
Seizures were induced in immature 18-day-old rats by i.p. administration of homocysteine (11 mmol/kg) and the effects of selected antagonists of NMDA receptors [MK-801 (0.5 mg/kg), AP7 (0.33 mmol/kg), CGP 40116 (10 mg/kg)] and non-NMDA receptors [GDEE (4 mmol/kg), NBQX (two doses, 30 mg/kg each)] were studied. The effect of MgSO4 (two doses, 2 mmol/kg each) was also tested. The anticonvulsant effect was evaluated not only from the behavioral manifestations of seizures, but also in terms of some indicators of brain energy metabolism. Rat pups were sacrificed during generalized clonic-tonic seizures, corresponding to 16-45 min after homocysteine administration. Comparable time intervals were used for sacrificing the pups which had received the protective drugs. In contrast to neonatal rats, in which only NMDA antagonists could prevent homocysteine-induced seizures, both NMDA and non-NMDA receptor antagonists exerted an anticonvulsant effect in 18-day-old rats. In addition, the pronounced anticonvulsant effect could be achieved by the combined treatment with low subthreshold doses of NMDA (MK-801) and non-NMDA (NBQX) receptor antagonists. The protection was evident not only in suppressing behavioral symptoms of seizures, but also in preventing most of the metabolic changes accompanying seizures, mainly glycogen degradation. More than a sevenfold accumulation of lactate occurring during seizures was markedly reduced by all the tested drugs, but was not completely eliminated. All antagonists, when given alone in the same doses as those used for seizure protection, remained without any effect on lactate levels. Comparison of the present data with previous findings concerning neonatal rats suggests that there may be a developmental change in anticonvulsant efficacy of non-NMDA receptor antagonists against homocysteine-induced seizures in rats.
Keywords: energetický metabolismus; Behavior, Animal; záchvaty; Male; neuroprotektivní látky; Rats, Wistar; Dizocilpine Maleate; dizocilpinmaleát; 2-amino-5-fosfonovalerát; chinoxaliny; vztah mezi dávkou a účinkem léčiva; Age Factors; Neuroprotective Agents; mužské pohlaví; Glutamates; potkani Wistar; Seizures; Anticonvulsants; krysa rodu Rattus; glutamáty; Animals; homocystein; Energy Metabolism; 2-Amino-5-phosphonovalerate; zvířata; mozek - chemie; Rats; antikonvulziva; věkové faktory; chování zvířat; Brain Chemistry; Homocysteine; antagonisté excitačních aminokyselin; Quinoxalines; Dose-Response Relationship, Drug; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; Excitatory Amino Acid Antagonists